The Responses of Religions Outside of Islam toward the Ecological Crisis: A Literature Review - Lalu Pattimura Farhan; Prosmala Hadisaputra (Millah: Journal of Religious Studies, 2022)
This article is the result of an online-based literature review. This study formulates the following question: what are the responses of religions outside Islam in Indonesia regarding the ecological crisis? The primary data of this study are articles from scientific journals that focus on theo-ecology from the perspectives of Christianity, Hinduism, Buddhism, and Confucianism. The data were obtained through the Google Scholar and DOAJ pages. This study finds that first, Christianity responds to the ecological crisis by presenting the theo-ecological concept as part of the affirmation of faith in God. The teaching of environmental conservation is a way of glorifying all of Godâ€™s creations. Second, Hinduism responds to the ecological crisis through its five teachings, namely Rta, Yadnya, Danu Ktih, Rwa Bhineda, and Tri Hita Karana, including Parhyangan Pawongan and Weakening. Third, Buddhism responds to environmental conservation with its teachings that emphasize the importance of beauty (aesthetics), as found in the Dhammapada-Khuddhaka NikÄya. Fourth, Confucianism responds to the ecological crisis through moral teachings such as protecting the environment.